Adaptation of the Enterprises of the Real Economy Sector to Supply Chain Management and Digitalization in the Conditions of the Development of Virtual Relations - Ukolov, Vladimir F.; Cherkasov, Vitaly V.; Ostrovskaya, Anna A. (ExcelingTech, 2019)
The article studies the insufficiently studied problem of adaptation of enterprises in the real sector of the economy to digitalization, in the conditions of active development of virtual relations. The author has set a goal - analyzing various aspects of this problem, to identify theoretical, practical features, the fundamental basis for the adaptation of enterprises in the real sector of the economy to digitalization and to develop a system of measures for its improvement. The aim of the research is the development and realization into practice of the basic theoretical principles and fundamental bases for the adaptation of enterprises in the real sector of the economy to supply chain strategy and digitalization, allowing them to become adaptive and more efficient. An analysis of a number of scientific primary sources devoted to the problem of adaptation allowed to the author not only to identify the essential foundations and features of the adaptation of enterprises in the real sector of the economy to digitalization, but also to establish its systemic nature of the simultaneous impact on all spheres of enterprises, their internal and external environment, which allows to develop a more balanced system of measures to improve it. The research used the methods of situational, structural and dynamic analysis, which provided an opportunity to study the adaptation of enterprises in the real sector of the economy to the conditions of supply chain strategy and digitalization, to trace its changes in time, in space and in close relationship with other phenomena. In assessing the state of adaptation of digital enterprises, a systematic approach was used. The exploration allowed to obtain scientific and practical results and conclusions, to identify the systemic nature of the impact of adaptation on all sides of the vital activity of enterprises in the real sector of the economy, on their internal and external environment of functioning, significative about the need to increase the role and responsibility of managers for the promotion of new managerial practices of adapting to digitalization and obtaining the expected results of the effectiveness of transformations. The practical significance of the research’s materials. Theoretical, practical features and the fundamentals of adaptation are used in practice, in the transition of enterprises in the real sector of the economy to digitalization. Their use contributes to the consolidation of the team into a single team, preserving the integrity of the enterprises of the real sector of the economy, increasing flexibility, sustainability, investment attractiveness, competitiveness and operating efficiency.